Metabolomic Characterization of Fatty Acids in Patients With Coronary Artery Ectasias - Liu, Tianlong; Sun, Yingying; Li, Hao; Xu, Haochen; Xiao, Ning; Wang, Xuliang; Song, Li; Bai, Congxia; Wen, Hongyan; Ge, Jing; Zhang, Yinhui; Song, Weihua; et al. (Frontiers in Physiology, 2021)
Background: We used a targeted metabolomics approach to identify fatty acids (FAs) metabolites that distinguished patients with coronary artery ectasia (CAE) from healthy Controls and patients with coronary artery disease (CAD). Materials and Methods: Two hundred fifty-two human subjects were enrolled in our study, including patients with CAE, patients with CAD and Controls. All the subjects were diagnosed by coronary angiography. Plasma metabolomic profiles of FAs were determined by a triple quadrupole mass spectrometric (UPLC-QqQ-MS/MS). Results: One hundred and three plasma metabolites were profiled in the discovery sets (n=72), including 36 metabolites of arachidonic acid(AA), eicosapentaenoic acid(EPA) and docosahexaenoic acid(DHA) , 10 FAs and 54 phospholipids. Among these metabolites, 36 metabolites of AA, EPA and DHA showed the largest difference between CAE and Controls or CAD. 12-hydroxyeicosatetraenoic acid (12-HETE), 17(S)-hydroxydocosahexaenoic acid (17-HDoHE), EPA, AA and 5-HETE were defined as a biomarker panel in peripheral blood to distinguish CAE from CAD and Controls in a discovery sets (n=72) and a validation sets (n=180). This biomarker panel had a better diagnostic performance than either metabolite alone in differentiating CAE from Controls and CAD. The areas under the ROC curve of the biomarker panel were 0.991 and 0.836 for CAE versus Controls, 1.00 and 0.904 for CAE versus CAD in the discovery and validation sets, respectively. Conclusions: Our findings revealed that the metabolic profiles of FAs in the plasma from patients with CAE can be distinguished from those of Controls and CAD. Differences in FAs metabolites may help to interpret pathological mechanisms of CAE.